Bosnia and Herzegovina : Fourth Review Under the Stand-By Arrangement and Request for Modification and Waivers of Applicability of Performance Criteria. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper focuses on Bosnia and Herzegovina's Fourth Review Under the Stand-By Arrangement and Request for Modification and Waivers of Applicability of Performance Criteria. Despite a challenging environment, steady progress has been made in meeting program objectives. All end-June 2013 performance criteria on fiscal balances were met. Although tax revenues have lagged the pick-up in activity, tight spending controls have allowed for the end-June 2013 quantitative performance criteria on the budget balances of the Institutions of Bosnia and Herzegovina and the central governments of the Federation and Republika Srpska (RS) to be met with comfortable margins. The IMF Staff recommends the completion of the fourth review.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet